Implementation of Arabic Language Learning for Children in Class III Madrasah Ibtidaiyah Negeri 3 Jember: Implementasi Pembelajaran Bahasa Arab Untuk Anak-anak di Kelas III Madrasah Ibtidaiyah Negeri 3 Jember (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2022)
Arabic language learning for children is a learning and teaching activity carried out by educators and students who are still in their childhood, so learning methods, learning strategies, learning media, teaching materials/ materials, evaluation techniques, and learning curricula are needed that are tailored for children. This article explains how the results of a mini-research that has been carried out by researchers to find out Arabic language learning in grade III at Madrasah Ibtidaiyah Negeri 3 Jember as a form of illustrating real Arabic learning in the field. This research uses a qualitative descriptive analysis method, which is a method of analyzing explicitly by describing or describing the data that has been collected in its actual state with a data collection method in the form of direct observation and interviews with teachers who teach Arabic subjects at the school. The mini-research found that the strategies used in learning Arabic in grade III madrasah Ibtidaiyah Negeri 3 Jember are lectures, question and answer, and quiz methods with whiteboard learning media, pasted pictures, and direct media. The Arabic learning material is adjusted to the material in the textbooks that follow KMA No. 183 of 2019 and the LKS book published by BUPIN and the evaluation technique uses oral guesses and evaluation questions in textbooks.